UJI BEBERAPA JENIS KOMPOS YANG TIDAK DAN DIBERI FUNGI MIKORIZA ARBUSKULA (FMA) TERHADAP PERTUMBUHAN DAN PRODUKSI PADI GOGO DI LAHAN MARGINAL (ULTISOL) - Yusnaweti MP (LPPM Universitas Muhammadiyah Sumatera Barat, 2016)
The experiment “Effects of Different Compost and Application Rate of Arbuscular Mychorhizae Fungi and No and Give on the Growth and Production of Upland Rice on Field Marinal (Ultisol)” is a field Sitiung, Dharmasraya, West Sumatera that was being done on the field and laboratory of Agriculture Faculty, University of Andalas, Padang. The objective is to obtain the many compost best Thitonia diversifolia compost, chiken compost and buffalo compost and Glomus fesciculatum of Arbuscular Mycorrhizaze Fungi (AMF) 0 and 5 g dosage for increasing growth and productivity of aerobic rice in Ultisol. This is a Factorial Experiment in Completely Random Blok Design, with two factors and four replications. The first factors are species of AMF, which is Glomus fasiculatum, or per planting hole. Variety of aerobic rice being used is Danau Gaung. Results of the experiment indicates that AMF from species Glomus fasiculatum with 5 g/ hol or planting hole and Thitonia diversifolia compost shows the best growth and highest uplan rice productivity in land Marginal (Ultisol).Sitiung, Dharmasraya. West Sumatera give 5.4 t/ha.Key words: Arbuscular Mycorrhizae Fungi (AMF), compost, upland rice and Ultisol